2016
DOI: 10.21061/jte.v27i2.a.4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Indicators Related to Constructs for Engineering Design Outcome

Abstract: With the publication of standards for teaching, learning, and the inculcation of technological literacy (International Technology Education Association, 2000), technology education in the United States has made a significant leap forward toward greater acceptance as a valid school subject. Standards represent content terrain claimed by a community of practitioners, and once stakes are put down, it is left to adherents to move in seeking title. It is doubtful whether we will witness a rush towards biotechnology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In JTE, five articles were examined, and Design as a domain was noted five times. Wilhelmsen and Dixon (2016) investigated "engineering design constructs identified by Childress and Rhodes (2008)" and concluded that "more questions still need to be answered. For example, can an instrument be developed from the indicators that validly and reliably assesses students' outcomes in design?…”
Section: Journal Analysismentioning
confidence: 99%
“…In JTE, five articles were examined, and Design as a domain was noted five times. Wilhelmsen and Dixon (2016) investigated "engineering design constructs identified by Childress and Rhodes (2008)" and concluded that "more questions still need to be answered. For example, can an instrument be developed from the indicators that validly and reliably assesses students' outcomes in design?…”
Section: Journal Analysismentioning
confidence: 99%
“…Within the technology education classroom over the past decade or so, engineering education in general and, more specifically, engineering design have been offered as keys to improving teaching and learning (Daugherty & Custer, 2012;Denson & Lammi, 2014;Lewis, 2005;Wicklein, 2006;Wilhelmsen & Dixon, 2016). This is reflected by both the Standards for Technological Literacy (STL) including engineering design in its standards (International Technology Education Association [ITEA], 2007) and the International Technology and Engineering Education Association, the professional association for the discipline, including engineering in its name.…”
mentioning
confidence: 99%